Identificação e caracterização de moléculas envolvidas na interação de Paracoccidioides brasiliensis com o hospedeiro - DANTAS, Sabrina Fonseca Ingênito Moreira (2009)
Paracoccidioides brasiliensis causes paracoccidioidomycosis (PCM), a systemic mycosis presenting clinical manifestations ranging from mild to severe forms. A P. brasiliensis cDNA expression library was produced and screened with pooled sera from PCM patients adsorbed against antigens derived from in vitro-grown P. brasiliensis yeast cells. Sequencing DNA inserts from clones reactive with PCM patients sera indicated 35 open reading frames presenting homology to genes involved in metabolic pathways, transport, among other predicted functions. The complete cDNAs encoding aromatic L-amino acid decarboxylase (Pbddc), lumazine synthase (Pbls) and a homologue of the high affinity copper transporter (Pbctr3) were obtained. Recombinant proteins PbDDC and PbLS were obtained; a peptide was synthesized for PbCTR3. The proteins and the synthetic peptide were recognized by sera of patients with confirmed PCM and not by sera of healthy patients. Using the vivo-induced antigen technology (IVIAT) we identified immunogenic proteins expressed at high levels during infection. Quantitative real - time RT-PCR demonstrated high transcript levels of Pbddc, Pbls and Pbctr3 in yeast cells infecting macrophages. Transcripts in yeast cells derived from spleen and liver of infected mice were also measured by qRT-PCR. Our results suggest a putative role for the immunogenic proteins in the infectious process of P. brasiliensis.